Simulation on Effects of Injection Parameters on CO2 Enhanced Gas Recovery in a Heterogeneous Natural Gas Reservoir. Issue 8 (8th July 2021) - Fan, Ling; Tan, Qizhi; Li, Hangyu; Xu, Jianchun; Wang, Xiaopu; Liu, Shuyang
Abstract: CO2 enhanced gas recovery (CO2 ‐EGR) is a promising technology to extract additional natural gas from depleted reservoirs with storing CO2 into underground formations. This work conducted CO2 ‐EGR simulations in a heterogeneous gas reservoir by using isothermal and non‐isothermal models and systematically analyzed the effects of various CO2 injection parameters on natural gas recovery, CO2 storage, and their comprehensive benefits. The results indicate that the CO2 injection well should be perforated in the lower position, whose overlaid layers with low permeability hinder the upward migration of CO2, and the larger natural gas recovery and CO2 storage can be achieved simultaneously for better comprehensive benefits. The optimal injection rate is 137.29 m 3 ·d −1 to achieve the highest recovery factor of 64.87%. The decrease in injection temperature and the increase in injection pressure are averse to the enhancement of recovery but beneficial to larger CO2 storage. The comprehensive benefits of natural gas recovery and CO2 storage are insensitive to the change of injection pressure and temperature, despite that every single one of them is more subjective to injection pressure than temperature. It's hoped that the findings of this work provide some theoretical guidance for the application of CO2 ‐EGR. Abstract : The isothermal and non‐isothermal CO2 ‐enhanced gas recovery (CO2 ‐EGR) simulations are performed in a heterogeneous natural gas reservoir. The effects of various CO2 injection parameters are analyzed on natural gas recovery and CO2 storage to provide insight on the choice of CO2 injection parameters of CO2 ‐EGR to obtain better benefits of fuel recovery and greenhouse gas mitigation.